The 95 Theses As Luther's Template for Reading Scripture - Wengert, Timothy J. (Lutheran quarterly, 2017)
Luther’s '95 Theses' has a rhetorical shape which reflects aspects of classical Renaissance rhetoric. In the Explanations of the 95 Theses Luther in fact labels two sections with technical names and writes his defense as if his arguments were meant to be read in this rhetorical light. These parts are traditionally, in this order, the exordium (introduction), the narration (basic, commonly accepted facts), the main thesis (summarized in Thesis 5), the proof or confirmation of this thesis and its corollaries, the refutation of anticipated objections, and the peroration. In the exordium, on which Luther puts great weight in his prefatory letter for the Explanations addressed to Pope Leo X, Luther writes that he is presenting these theses “out of love and zeal for the truth.” The proof of his work stretches from theses 6-80, and a rejection or confutation of other opinions - placed in the mouth of a sharp layperson - comes in theses 81-91. Crucial for Luther’s interpretation of scripture, however, comes in the narration and the peroration: theses 1-4 and 92-95. Precisely where Luther sets forth the incontrovertible facts at the beginning and a summary of his argument at the end, he calls upon scripture. The argument of the Theses serves in turn as a template for reading scripture theologically.